Livelihood diversification as key to long-term non-migration: evidence from coastal Bangladesh - Bangkim Biswas; Bishawjit Mallick (Environment, Development and Sustainability, 2020)
Understanding how livelihood diversification contributes to long-term non-migration decisions of people at risks is innovative and timely in the context of future climate change adaptation planning. This study particularly examines this question and explores how and to what extent livelihood diversification in the face of climate change can support long-term non-migration for people living in the southwest coastal region of Bangladesh. We employed a cluster random sampling method to select the respondents and interviewed a total of 183 households by using a structured questionnaire. Analysis indicates that the tendency of livelihood diversification based on shrimp-farming has been intensified in recent years as the land use pattern also changed due to the frequent occurrence of environmental hazards. The Poisson regression model states that belonging to a religious minority and shrimp farming determines the extent of livelihood diversification, i.e., if the person belongs to a minority religion and possesses a shrimp-farm they will have more diversified sources of income compared to others living in the society. Moreover, therefore, one in every three households in these studied communities' practices seasonal migration as an alternative livelihood strategy so that their family can stay put. The outcome of this study motivates the government and non-government organizations to take policies and programs in a direction that may reduce the dependency on seasonal migration and introduce locally adoptable diversified employment opportunities.
Keywords: 330; Livelihood diversification; Long-term non-migration; Seasonal migration; Coastal Bangladesh